Financial situation of PN17 companies listed in the Malaysian Stock Exchange - Mohammed, Ali Abusalah Elmabrok (2012)
A Practice Note 17 (PN17) Company is a listed company in the Malaysian Stock Exchange that is financially distressed or does not have a core business or has failed to meet minimum capital or equity (Less than 25% of the paid up capital). Financial ratio analysis method can be used to detect the failure of this company. As of 9th August 2010, there are still thirty four companies listed on Malaysian Stock Exchange classified under PN17 List. These companies have entered into PN 17 list in accordance with existing standards. There are also investors who do not know the status of these listed companies. A real and full attention has not been given yet for these companies. Analytical studies and scientific researches are almost still lacking on PN17 Companies listed in the Malaysian Stock Exchange. The aims of this research work is to examine the differences between the financial liquidity ratios (Current, Quick, Cash Ratio) and Altman's Z-score in determining the financial failure of companies, that is using financial ratios and Altman Z Score to examine whether there is different between PN17 companies and Non-PN17 listed in the Malaysian Stock Exchange. It also aimed to determine whether are all the PN17 Companies listed in the Malaysian Stock Exchange financial failure companies, to explore and report the financial situation of companies listed on Malaysian Stock Exchange. The available data collected from the library of Malaysian Stock Exchange covering the period from 2003 to 2009 were used in the analysis. This study answered the research questions formulated. Financial Liquidity ratios and Altman Z-score can be used to detect financial distress of companies, and it is important to compare ratios with the industry average or with a competitor in the same sector. Not all the PN17 Companies are financial failure Companies, It was found that there are financial difficulties companies still listed among the Non-PN17 list. Companies should emphasize on the issue of accounting disclosure.